u'' - u = epsilon * t*u

t>0, u(0) = 1, u'(0) = -1

Find the exact solution.

I know we need to use the method of undetermined coefficients, but not sure how to make it work out properly. Any help would be great, thanks!

Printable View

- Oct 8th 2008, 07:20 PM860DefDifferntial Equation Help
u'' - u = epsilon * t*u

t>0, u(0) = 1, u'(0) = -1

Find the exact solution.

I know we need to use the method of undetermined coefficients, but not sure how to make it work out properly. Any help would be great, thanks! - Oct 8th 2008, 07:28 PMJhevon
- Oct 9th 2008, 04:22 AM860Def
sorry, i was just using the * to indicate multiplication. epsilon is also just a constant. so let's have epsilon = some constant a, then we'll have

u'' - u = atu

t>0, u(0) = 1, u'(0) = -1

hope that clears my question up a little bit.